Internalisasi Nilai dan Kontrol Sosial Berbasis Simbol dalam Praktik Songko’ Recca Bugis - Adnan Achiruddin Saleh; Nurul Fajriani; Nur Syafhirah Syam Jayadi; M. Alfatir; Runik Machfiroh (Journal of Society Counseling, 2026)
This study examines the role of songko’ recca, a traditional Bugis headwear, as a mechanism of value internalization and informal social control within the community. Using a qualitative case study approach, data were collected through semi-structured interviews, observation, and visual documentation. The findings reveal that songko’ recca functions beyond a cultural or religious symbol, serving as a medium through which social and religious values are internalized into individual consciousness. Through repeated use and shared meanings, the symbol fosters self-regulation, encouraging individuals to align their behavior with societal norms. Additionally, songko’ recca operates as an informal social control mechanism by generating social expectations, symbolic surveillance, and collective judgment in everyday interactions. The study demonstrates that symbolic practices can simultaneously shape internal awareness and regulate external behavior. Theoretically, this research integrates perspectives of symbolic interactionism, value internalization, and social control to explain how cultural symbols function as active agents in social life. Practically, the findings highlight the potential of culturally embedded symbols in developing context-based approaches within Community Counseling and Cross-Cultural Counseling. This study contributes to expanding the understanding of religious symbols as dynamic mechanisms for psychosocial regulation in society.